Coordinated frequency support strategy for VSC-HVDC integrated offshore wind farm system - Li, He; Li, Yuekai; Meng, Yao; Yan, Kefei (Frontiers in Energy Research, 2024)
The large-scale offshore wind power integrated into the onshore power grid through voltage source converter-based high voltage direct current (VSC-HVDC) system is unable to provide inertia response and frequency support to the onshore power grid. To improve the frequency characteristics of the receiving-end power grid, a coordinated frequency control strategy combining VSC-HVDC and offshore wind power is proposed. The onshore converter adopts virtual inertia control, which uses DC capacitors to absorb or release energy for inertia support after the receiving-end grid is disturbed. Wind-farm-side VSC (WFVSC) obtains the frequency signal of the receiving-end power grid by detecting the local DC voltage. The offshore wind farm (OWF) transfers the frequency deviation into an additional power signal and sends it to the power controller to adjust the output, thereby performing inertia and primary frequency response. In addition, a secondary frequency regulation strategy for wind farms has been designed to achieve non-difference frequency regulation of the receiving-end power grid. Finally, a simulation model of VSC-HVDC integrated OWF system is constructed to demonstrate the proposed coordinated frequency control strategy for VSC-HVDC and OWF. The results indicate that the proposed control strategy can effectively enhance the frequency support capability of the receiving-end power grid.